Morphology and localization of carbonic anhydrase in the alimentary canal of the Swedish house cricket, Acheta domesticus (Orthoptera: Gryllidae) - Thorsson, Elina (SLU/Dept. of Anatomy, Physiology and Biochemistry (until 231231), 2018)
There is a growing interest in using insects as part of the human diet. Actors such as the Swedish University of Agricultural Sciences (SLU) and Nordic Food Labs are investigating the potential use of insects as a source of protein and nutrients for the western human population. This degree project in veterinary medicine is part of the SLU project; Eating crickets- an appetizing solution for today´s global problems which aims to develop a new sustainable protein source based on the Swedish house cricket, A. domesticus. Important aspects within the project are sustainability, biodiversity, nutrition, ethics, food safety and acceptance (SLU 2017). To produce a food that achieves this, we need to know more about the food source itself. How does the metabolism of the house cricket work and more precisely how does its alimentary canal work? This project aims to describe the morphology of the alimentary canal of the Swedish house cricket and to investigate the activity of the enzyme family of carbonic anhydrases (CA) along its entire length.In the main study 20 conventionally bred crickets, at the age of 40-45 days, were used. The crickets were divided into two groups, equal distribution in terms of sex, and one group was left to starve for 36h whereas the other group was fed. Apart from this treatment the same protocol was used for both groups. After being euthanized (anesthetized with CO2 and then decapitated) the alimentary canal was dissected, anatomical data was collected, and the tissue samples were prepared for histological examination. Segments from all parts of the gut were stained with HE and for carbonic anhydrase. Slides were evaluated using light microscopy.In this study the alimentary canal of A. domesticus has for the first time been described in its entirety, both anatomically and histologically. The alimentary canal of A. domesticus is very similar to the gut of other species within the Gryllidae family. The results suggest the presence of goblet cells forming gastric glands in the midgut epithelium. To confirm the presence of goblet cells and investigate the constitution of the possible gastric glands additional histological examination with PAS-staining is needed. No significant results were obtained regarding differences between groups including males compared to females and fed individuals compared to starved. If the study is repeated more care should be taken to have crickets of as similar age as possible and increase the size of the groups. The localization of active CA has been demonstrated in the striated muscle along the entire alimentary canal and in the epithelium of the ceaca and ventriculus. CA activity is found in the membrane of the majority of the columnar epithelial cells in the midgut suggesting that CA is associated to the most numerous cell type, the enterocyte. In order to determine which cell type/ cell types that contains CA additional histological examination is needed. There are possible sex differences regarding CA activity in the midgut. Starved males showed none to weak black staining compared to the much stronger staining in the epithelium of starved females. To confirm the results of possible sex differences the study needs to be repeated with increased group sizes. It is suggested that CA in the alimentary canal of A. domesticus may contribute to acid-base balance in both muscle and gut lumen. Future experiments with ion selective microelectrodes and presence/ absence of CA inhibitors may be a way to test this hypothesis.